Annual Plan 1994-95 - Planning Commission (Planning Commission, 1994)
The stabilisation and structural adjustment measures, initiated since July, 1991 by now commonly referred to as "Economic Reforms" mark a watershed in the country's economic policies. For almost three decades since Independence, India’s development strategy and economic policy were guided by the objectives of accelerating the growth of output and employment but with social justice and equity.
Government of India Planning Commission
Government of India Planning Commission